Bioactive compounds and sensorial analysis of functional drink from purple corn (Zea mays L.) and stevia (Stevia sp.) - Bonilla, Pablo E. (2015)
In the present study were evaluated the bioactive compounds and antioxidant activity and satisfaction degree of a drink made with purple corn and stevia. Were used HPLC, ABTS, ORAC, DPPH methods and was done comparison according to the hedonic scale. Results showed close phenolic compounds to 2 mg/mL, high in anthocyanins (50,84 mg/100 mL) and antioxidant activity with ABTS (TEAC 17,96 pmol/mL), ORAC (31,01 μmol TEAC/mL) and DPPH (GAE 0,706 mg/mL). The useful life assessment revealed a synergistic effect between the purple corn anthocyanins and the active components of stevia. The satisfaction degree revealed that the formulation was described between "really like " (19%) and "like slightly " (33%) according to the hedonic scale about attributes of color, smell, taste and overall acceptability.